Factors influences investment decision and portfolio construction (DSE Perspective) and a study on IDLC Investments Limited - Dey, Debasish (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.